Snorkellers’ environmentally conscious behaviour after visiting the Great Barrier Reef - Pabel, Anja; Cassidy, Leonie J.; Prideaux, Bruce R. (Asia Pacific journal of tourism research, 2023)
The majority of tourists who visit Australia’s Great Barrier Reef (GBR) engage in snorkelling. Yet little is known about how snorkellers perceive this experience. The aim of this study was to investigate snorkeller behaviour by exploring their environmental opinions and to provide insights on the association between climate concerns and environmentally conscious behaviours of snorkellers. A self-administered questionnaire (n = 273) was distributed onboard reef tourism vessels visiting the study area. Approximately one-third of respondents believe that climate change and global warming are major threats to the GBR. Regression results indicate the environmentally conscious behaviour model (ECBM), a modified version of the norm activation model, is effective in understanding how a snorkeller’s level of climate concern (LCC) both directly and indirectly activates and influences a snorkeller’s environmentally conscious behaviour (ECB). LCC has a positive direct effect on ECB, and a positive indirect effect via environmental identity (EI), and personal environmental norms (PEN).